Durable control of metastatic AKT1-mutant WHO grade 1 meningothelial meningioma by the AKT inhibitor, AZD5363 - Weller, Michael; Sahm, Felix; Deimling, Andreas von (Journal of the National Cancer Institute, 2017)
Abstract. High-throughput analyses have revealed the presence of activating mutations in the AKT1 gene in a subpopulation of meningiomas. We report a female pa